Business and Human Rights in ASEAN: Lessons from the Palm Oil Sector in Malaysia - Andika AB. Wahab (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2019)
The release of the United Nations Guiding Principles on Business and Human Rights in 2011 aims to address gaps in human rights governance by setting a standard and corporate culture of respecting human rights. As part of the state responsibility to implement these guiding principles, some member states of the Association of Southeast Asian Nations (ASEAN) have already embarked preliminary steps towards establishing their respective National Action Plan on Business and Human rights (NAPBHR), while others are still lag behind. This article describes current development on business and human rights in the region. Drawing from the palm oil sector’s experience in Malaysia, this study aims to provide lessons for ASEAN member states to contemplate when developing their NAPBHR. In this article, I argue that while some large palm oil companies have shown modest progress in realizing their human rights obligation, challenges emerge in many forms including the lack of leadership, collaboration and ambition to steer and scale up industry transformation on human rights across supply chain. Equally important, challenges around certification scheme depict that it is not the only solution in persuading respect to human rights. Meaningful values transfer often overlooked in certification practice resulting in typical